2010
DOI: 10.1002/ldr.1043
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of landscape restoration along a degraded urban streamside

Abstract: Restoration of degraded lands in urban areas increases the ecologic, aesthetic and economic value of these areas and contributes to quality of life in cities. This study explores public attitudes towards restoration of a derelict urban streamside corridor. Data for this study were collected using a social survey among users and neighbourhood residents of the Ç ayboyu area in Isparta, Turkey. The survey compared the previous and present situation of the survey site in order to reveal the influence of stream res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Positive interactions of people with natural areas can promote an affinity for the environment and its conservation and improvement (Spirn 1988, Purcell et al 2002, Turner et al 2004, Beatley 2011, Özgüner et al 2012. The USR framework uses increased flexibility for setting ecological and societal objectives (by avoiding an ecologically focused reference-condition approach) to achieve additional ecological and societal outcomes.…”
Section: Urban Stream Renovationmentioning
confidence: 99%
“…Positive interactions of people with natural areas can promote an affinity for the environment and its conservation and improvement (Spirn 1988, Purcell et al 2002, Turner et al 2004, Beatley 2011, Özgüner et al 2012. The USR framework uses increased flexibility for setting ecological and societal objectives (by avoiding an ecologically focused reference-condition approach) to achieve additional ecological and societal outcomes.…”
Section: Urban Stream Renovationmentioning
confidence: 99%
“…Monarca et al ., ; El Baroudy, ). Finally, socioeconomic factors in peri‐urban areas impact the environment more rapidly than in rural areas (Aguilar & Santos, ; Özgüner et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Integrating both knowledge bases encourages the investigation of potential uncertainties, the development of a more rigorous analysis (Reed, ; Mekuria & Aynekulu, ; Jones et al, ; Tesfaye et al, ; Mulale et al, ) and enhances the planning process effectiveness (Gadgil & Ede, ; Bewket & Sterk, ; Reed et al, ; Reynolds et al, ; Nabahungu & Visser, ; Fleskens & Stringer, ). Previous studies have shown that integration between science and local knowledge positively influences the social, economic and environmental aspects of local communities (Özgüner et al, ; Karltun et al, ; Nabahungu & Visser, ; Sop & Oldeland, ; Bisaro et al, ; De Pina Tavares et al, ). In addition, public participation in policy making has important advantages in the democratic development and implementation of management actions.…”
Section: Introductionmentioning
confidence: 99%